Science as the Last Dogma: An Ironic Reflection - Doepp, Manfred (British Journal of Healthcare and Medical Research, 2024)
There are several crises in our world, the allegedly dangerous content of which was initiated by scientists. Ever since the Club of Rome proclaimed the climate crisis in 1972 ("The Limits to Growth", 1,2), we have lived in fear that normal life on earth will soon no longer be possible. If it was acid rain back then, today it is CO2 production, always man-made. Until recently, we lived in fear of the Covid-19 virus and around 2/3 of people underwent an insufficiently tested and probably dangerous vaccination, the composition of which was unclear. Today, we are astonished to see excess mortality and "post-vac syndrome". Conclusion : We should be suspicious when "The Science" publishes something. It may not be the truth.